الشرقي في المنظور الغربي ( قراءة في ثلاثية أرض السواد لعبد الرحمان منيف - عبيد, عائشة (جامعة الوادي - university of Eloued, 2022)
ملخص تعد مسألة الصراع الحضاري بين الشرق والغرب قضية قديمة و معقدة، بل إنها من أكثر المسائل تعقيدا و إثارة للجدل عند العديد من الدارسين في مختلف المجالات. ويعد عبد الرحمان منيف من أهم الأدباء الذين اهتموا بهذه القضية من خلال إبداعاته،التي جعلها محورا أساسيا للكشف عن علاقة الشرق بالغرب، أو بالأحرى علاقة الأنا بالآخر. وهذا ما نجده في ثلاثيته أرض السواد خاصة. فكيف صور لنا منيف علاقة الغربي بالشرقي من خلال هذا العمل؟ وما هي نظرة الغربي للشرقي عموما- حسب رأيه-؟ هذا ما تهدف هذه الدراسة للإجابة عنه، من خلال اتباع المنهج التحليلي. Abstract: The issue of the civilizational conflict between East and West is an old and complex issue, but rather one of the most complex an controversial issues for many scholars in various fields. Abd al-Rahman Munif is considered one of the most important writers who paid attention to thi issue through his creations, which made it an essential focus for revealing the relationship of the East to the West, or rather the relationship of th ego to the other. This is what we find in his trilogy, the land of blackness in particular. How did Munif portray the relationship between the Western and the Eastern through this work? What is the Western view of the Eastern in general - according to his opinion -? This is what this study aims .to answer, by following the analytical method.
،the Eastern In The Western Perspective (reading In The Trilogy Of The Land Of Blackness By Abd Al-rahman Munif)
مقال
Keywords: الأنا، الآخر، الشرق، الغرب، الصراع، أرض السواد; The ego, the other, the east, the west, the conflict, the land of blackness.